2017
DOI: 10.22516/25007440.128
|View full text |Cite
|
Sign up to set email alerts
|

Medicamentos causantes de hepatotoxicidad en el embarazo: revisión estructurada

Abstract: Objetivo: identificar los medicamentos y determinar las principales características asociadas con hepatotoxicidad por medicamentos en el embarazo.Método: revisión estructurada en PubMed/Medline, EMBASE y Web of Science utilizando los términos: Drug induced liver injury OR Hepatotoxicity AND Pregnancy. La búsqueda incluyó artículos en inglés, español, humanos, entre 2005 y 2015, con información sobre hepatotoxicidad por medicamentos en el embarazo. Fueron excluidos los artículos sin relación con embarazo o hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…NVP's associated hepatotoxicity in the clinics (case reports, clinical trials and cohorts' studies) has been reviewed in detail elsewhere [63]. A structured review of the literature (2005-2015) also revealed that NVP causes hepatotoxicity in pregnant patients, manifested as elevation of transaminases, rash, hepatitis, pruritus, abdominal pain, eosinophilia, encephalopathy, and jaundice [64]. The link between NVP and more advanced stages of liver disease has also been assessed through studies with HCV-coinfected patients, obtaining somewhat contradictory results.…”
Section: Nevirapinementioning
confidence: 99%
“…NVP's associated hepatotoxicity in the clinics (case reports, clinical trials and cohorts' studies) has been reviewed in detail elsewhere [63]. A structured review of the literature (2005-2015) also revealed that NVP causes hepatotoxicity in pregnant patients, manifested as elevation of transaminases, rash, hepatitis, pruritus, abdominal pain, eosinophilia, encephalopathy, and jaundice [64]. The link between NVP and more advanced stages of liver disease has also been assessed through studies with HCV-coinfected patients, obtaining somewhat contradictory results.…”
Section: Nevirapinementioning
confidence: 99%